Plasmatic Soluble Receptor for Advanced Glycation End Products as a New Oxidative Stress Biomarker in Patients with Prosthetic-Joint-Associated Infections?. (13th December 2017) - Massaccesi, Luca; Bonomelli, Barbara; Marazzi, Monica Gioia; Drago, Lorenzo; Romanelli, Massimiliano Marco Corsi; Erba, Daniela; Papini, Nadia; Barassi, Alessandra; Goi, Giancarlo; Galliera, Emanuela
Abstract : Prosthetic joint infection (PJI) is the most common cause of failure of total joint arthroplasty, but a gold standard for PJI diagnosis is still lacking. Advanced glycation end products (AGEs) are proinflammatory molecules inducing intracellular oxidative stress (OS) after binding to their cell membrane receptors (RAGE). The aim of this study was to evaluate plasmatic soluble receptor for advanced glycation end products (sRAGE), as a new OS and infection marker correlating sRAGE to the level of OS and antioxidant defenses, in PJI, in order to explore the possible application of this new biomarker in the early diagnosis of PJI. Plasmatic sRAGE levels (by ELISA assay), plasma antioxidant total defenses (by lag time method), plasma reactive oxygen species (ROS), and thiobarbituric acid reactive substance (TBARS) levels (by colorimetric assay) were evaluated in 11 PJI patients and in 30 matched controls. ROS and TBARS were significantly higher (p < 0.001 ) while plasma total antioxidant capacity and sRAGE were significantly lower (p < 0.01 ) in patients with PJI compared to controls. Our results confirm the OS in PJI and show a strong negative correlation between the level of sRAGE and oxidative status, suggesting the plasmatic sRAGE as a potential marker for improving PJI early diagnosis.